Monoclonal antibody (Y1/82A) with specificity towards peripheral blood monocytes and tissue macrophages. Issue 7 (July 1988) - Davey, F R; Cordell, J L; Erber, W N; Pulford, K A; Gatter, K C; Mason, D Y
Abstract : A new monoclonal antibody, Y1/82A, was raised against phytohaemagglutinin activated peripheral blood mononuclear cells. Using an immunohistochemical technique it was shown that Y1/82A reacts against peripheral blood and bone marrow monocytes and resident macrophages from essentially all human tissues. Y1/82A bound to determinants present in leukaemic cells from patients with acute myelomonocytic leukaemia and acute monocytic leukaemia, but not to neoplastic cells from patients with malignant lymphoproliferative disorders or malignant epithelial tumours. Y1/82A failed to react with other cell types, with the exception of osteoclasts and megakaryocytes. Analysis by Western blotting showed that the antigen detected by antibody Y1/82A was associated with intracellular granules in macrophages. Monoclonal antibody Y1/82A may be useful in the diagnosis of monocytic leukaemias and histiocytic neoplasms and in the identification of macrophages in tissues from various inflammatory and neoplastic conditions.